Pengaruh Kompetensi Literasi Digital dan Komunikasi yang Intensif terhadap Kinerja Pegawai Negeri Sipil dengan Sistem Kerja Tim sebagai Variabel Intervening - Keri Handayani; Adijati Utaminingsih; Djoko Santoso (Syntax Corporation Indonesia, 2024)
This research aims to analyze the influence of digital literacy competency and intensive communication on the performance of civil servants using the teamwork system as an intervening variable. The independent variables in this research are Digital Literacy and Intensive Communication Competence, the dependent variable is Employee Performance and the mediating variable is Teamwork System. This research uses quantitative methods with the help of questionnaires for data collection. The research was conducted at the Regional Office of the Ministry of Religion of Central Java Province, with a population of 156 people. The sample was carried out using a survey method. The data analysis technique used was Structural Equation Modeling (SEM), with a Partial Least Squares (PLS) approach. It was concluded that the intensive Digital Literacy and Communication Competency variables had a positive and significant influence on Employee Performance. The Teamwork System mediates Digital Literacy Competency and Intensive Communication on Employee Performance through the help of technology. This reflects that Digital Literacy Competence and intensive communication between employees are important in completing all work. Agencies must encourage employees to improve their competence both personally and through regular training mechanisms held by the agency. So that all employees are able to complete the work they are responsible for well without having to rely or rely on other parties.